PSYCHOLOGICAL MEDIATORS BETWEEN PAIN AND SELF-REPORTED HEALTH IN ELITE ATHLETIC ATHLETES: A CROSS-SECTIONAL STUDY TO INFORM OVERUSE INJURY PREVENTION. Issue 7 (11th March 2014) - Timpka, T; Dahlström, Ö; Bergdahl, M; Lundgren, D; Bargoria, V; Jacobsson, J
Abstract : Background: Understanding how sensations of pain affect health status appraisal among athletics athletes is of importance for prevention of overuse injuries. Identification of psychological mediators of the association opens for new intervention possibilities. Objective: To examine psychological mediators of the association between pain and self-reported health in elite athletics athletes. Design: Cross-sectional study using e-epidemiological survey methods. Setting: Swedish male and female youth and adult elite athletics athletes. Participants: Athletics athletes ranked in the national top-10 were invited (n=301). 226 (75%) athletes returned complete data. Risk factor assessment: Pain measured on a 3-graded scale; the psychological mediators perceived motivational climate (measured by the PMCSQ), coping behavior (Brief Cope), body consciousness and hyperactivity (BCS-ADHD), and commitment to exercise (CES). Main outcome easurements: Self-reported health (EuroQol-5D). Results: 85 (38%) athletes reported experiencing pain at the time of the study. The level of pain was associated with the self-reported health (P<.001); the strength of the association did not differ between men and women (P=.720). A multi-component model of psychological elements mediating the association between pain and self-rated health included body competence (Mediation Effect (ME) −1.053 (90% CI −2.025 – −0.082), private body consciousness (ME –0.744 (90% CI –1.478 – −0.010), and a perceived motivational climate endorsing mastery (ME –0.623 (90% CI –1.229 – −0.017). No influence from gender or age on the mediating effects could be statistically confirmed. Conclusions: Awareness of internal sensations (private body consciousness), an affirmative evaluation of own body functions (body competence), and a perceived endorsement of athletic development (mastery) augmented the influence of pain on self-reported health among elite athletic athletes. This paradoxical observation warrants further investigation in prospective studies on associations between pain, perceived health, athlete and coach behaviors, and overuse injury in elite athletics athletes.